Pembelajaran Sastra Indonesia Berbasis Ekokritik Sebagai Media Edukasi Nilai Kearifan Lokal dan Kesadaran Lingkungan di Sekolah - Jafar, Jafar; Rosary Iriany; Nuzul Tenriana; Andi Muhdar (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the relationship between literature, ecology, and Indonesian culture through an ecocritical approach. Literature is understood not only as an aesthetic work but also as a representation of the relationship between humans, nature, and their social environment. The ecological approach to literature views literary texts as reflections of ecological awareness and cultural values that shape how humans perceive and treat nature. This research employs a qualitative descriptive method using a literature review technique. The data were obtained from Indonesian literary works with ecological themes, such as Orang-Orang Proyek by Ahmad Tohari and Nyanyian Rimba by Triyanto Triwikromo, as well as relevant references on literary ecology and Indonesian cultural studies. The analysis focuses on identifying the representation of ecological values in the literary texts, emphasizing the interconnections among humans, culture, and the environment. The results indicate that Indonesian literary works convey ecological values such as harmony between humans and nature, local wisdom, mutual cooperation (gotong royong), simplicity, and environmental responsibility. Literature functions as a cultural archive that records the ecological worldview of traditional communities while also serving as a medium for reflection and critique of environmental crises caused by modernization. Furthermore, literature holds significant potential in fostering ecological awareness and sustainability ethics through the promotion of cultural values. Thus, literary ecology plays a vital role in understanding and revitalizing cultural practices to be more in harmony with nature and in strengthening the function of literature as a medium for cultivating ecological consciousness among students at MA Arifah Gowa.